The Effectiveness of the Roles of Liaison Officers and Business Consultants in the Development of Alna Mochi and My Crepes MSMEs - Sarah Suhaila (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effectiveness of the roles of the Liaison Officer (LO) and Business Consultant (BC) in supporting the development of the micro, small, and medium enterprises (MSMEs) Alna Mochi and My Crepes through the Polbeng Business Expo Chapter II. The research employed a qualitative method with a project-based approach consisting of three stages: preparation, implementation, and completion. Data were collected through direct observation, semi-structured interviews, and documentation during the mentoring activities. During the preparation stage, the team identified the business needs and challenges faced by both MSMEs and developed mentoring plans. In the implementation stage, the Liaison Officer facilitated communication, coordination, and operational activities between the organizing committee and MSME owners, ensuring that all activities were carried out effectively. Meanwhile, the Business Consultant provided assistance in developing digital marketing strategies, creating promotional materials, implementing QRIS-based digital payment systems, and improving basic business management practices. The completion stage involved evaluating the mentoring outcomes and documenting the results. The findings indicate that the collaboration between the Liaison Officer and Business Consultant positively contributed to increasing product visibility, expanding market reach, improving digital technology adoption, facilitating cashless transactions, and enhancing the professionalism of the MSMEs. Although the mentoring period was relatively short, the integrated roles of both mentors effectively supported the business growth and sustainable development of Alna Mochi and My Crepes while strengthening their competitiveness in the increasingly digital business environment.